Molecular Function of Tocopherols in Age Related Diseases - YILMAZ, BETÜL; KARTAL ÖZER, NESRİN (BENTHAM SCIENCE PUBL LTD, 2014)
Tocopherols, with a phytyl side chain in its chroman ring, belong to vitamin E family and have several effects on organisms. They are also classified as therapeutics against different types of human diseases. Especially important roles in cell signaling and gene regulatory mechanisms make tocopherols crucial as therapeutic agents. Aging is accompanied with several degenerative disorders including cardiovascular, neuronal and metabolic diseases. The role of free radical damage in aging has been identified and tocopherols were shown to be involved in age related disorders. Recent studies and future directions will be focused in this review regarding the molecular functions of tocopherols.
Keywords: Tocopherol; aging; atherosclerosis; Alzheimer's disease; nonalcoholic fatty liver disease; FATTY LIVER-DISEASE; SCAVENGER RECEPTOR EXPRESSION; VITAMIN-E CONSUMPTION; SMOOTH-MUSCLE-CELLS; D-ALPHA-TOCOPHEROL; KINASE-C-ALPHA; ALZHEIMERS-DISEASE; OXIDATIVE STRESS; NONALCOHOLIC STEATOHEPATITIS; TRANSFER PROTEIN